Pengembangan Multimedia Interaktif Materi Sistem Peredaran Darah Manusia Untuk Kelas V Sekolah Dasar - Munawaroh, Isnaini; Sulthoni, Sulthoni; Susilaningsih, Susilaningsih (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
Interactive multimedia is a learning medium that presents the material with a combination of text, images, audio, video, and animation. The purpose of this research and development is to produce an interactive multimedia product that is valid, feasible, and effective for learning activities on the human circulatory system material at the elementary school level. The method used in this research is Research and Development (R&D) with the Lee & Owens development model consists of 5 stages as follows: (1) analysis, (2) planning, (3) development, (4) implementation, (5) evaluation. The validation stage was carried out on media experts and material experts and then tested on 19 grade V students of SDN Tamiajeng. The results of interactive multimedia development were declared valid with the percentage of media experts was 98.61%, 79.16% of material experts, 82.98% small group trials, 84.36% large group trials. Interactive multimedia is declared effective for learning by obtaining a percentage of 84.21%. Because of this finding, it can be concluded that interactive multimedia material on the human circulatory system produces valid, feasible, and effective categories to be used for learning.AbstrakMultimedia interaktif merupakan media pembelajaran yang menyajikan materi dengan adanya kombinasi teks, gambar, audio, video dan animasi. Tujuan penelitian dan pengembangan ini untuk menghasilkan suatu produk multimedia interaktif yang valid, layak dan efektif digunakan untuk kegiatan pembelajaran pada materi sistem peredaran darah manusia di jenjang sekolah dasar. Metode yang digunakan pada penelitian ini adalah Research and Development (R&D) dengan model pengembangan Lee & Owens yang terdiri dari 5 tahapan sebagai berikut: (1) analisis, (2) perencanaan, (3) pengembangan, (4) implementasi, (5) evaluasi. Tahap validasi dilakukan kepada ahli media dan ahli materi kemudian di uji cobakan kepada 19 siswa kelas V SDN Tamiajeng. Hasil pengembangan multimedia interaktif dinyatakan valid dengan presentase sebesar 98,61% dari ahli media, 79,16% dari ahli materi, 82,98 uji coba kelompok kecil, 84,36% uji coba kelompok besar. Multimedia interaktif dinyatakan efektif digunakan untuk pembelajaran dengan memperoleh presentase sebesar 84,21%. Sehingga dapat disimpulkan bahwa multimedia interaktif materi sistem peredaran darah manusia menghasilkan kategori valid, layak dan efektif digunakan untuk pembelajaran.